Susceptibility pattern of pediatric uropathogens: Insights from Mirpur Azad Jammu Kashmir Pakistan - Manzoor, Ammara; Ahmed, Toqeer; Batool, Syeda Tahira; Chaudhry, Nabia; Khurshid, Fatima (Infectious Diseases Journal of Pakistan, 2024)
Background: Antibiotic resistance in pediatric urinary tract infections (UTIs) is a growing concern, necessitating the assessment of antibiotic susceptibility profiles for effective treatment strategies. The study was designed to assess the clinical profile, common uropathogens causing UTI and their antimicrobial susceptibility patterns. The study was designed to assess the frequency of pediatric UTIs along with antimicrobial susceptibility pattern of the isolated uropathogens. Material and Methods: We conducted a retrospective review of clinical records at DHQ Hospital Mirpur AJK, Pakistan from March to September 2023, focusing on urinary tract infections in pediatric patients. We identified uropathogens and their antimicrobial susceptibility pattern to guide effective treatment strategies and address drug resistance. Results: Data was collected from the medical records of 140 pediatric patients. of which, 49% (n=69) had positive urine cultures. Majority of these patients were males (71%). The most predominant organism was Klebsiella pneumoniae (32%) followed by, Staphylococcus aureus (26%), Escherichia coli (22%) and Enterococcus faecalis (11%). Mixed growth of uropathogens was seen in 9% of the cases. Regarding Antimicrobial susceptibility pattern, Amikacin, Vancomycin, Neomycin and Tigecycline were the most susceptible (100%), followed by chloramphenicol (90.9%), Linezolid (83.4%), Rifampicin (82%), Meropenem (77.3%), Nitrofurantoin (70%), Tazobactam (68.7%) and Imipenem (68.4%). Cephalexin (66.7%), Gentamicin (63.6%) and Cefipime (50%) showed moderate susceptibility. Whereas, Sulfamethoxazole (35%), Levofloxacin (31.4%), Cefoxitin (26.3%), Ciprofloxacin (22.2%), Tetracycline (20.5%), Cefuroxime (14.2%), Ceftriaxone (9.52%) and Amoxicillin (9.52%) were the least susceptible. Conclusion: Our research suggests that it is important to review the use of antibiotics for treating UTIs in pediatric patients due to changes in antibiotic susceptibility and the increase in resistance among bacteria. This emphasizes the significance of antimicrobial stewardship. Keywords: Urinary tract infections. Antimicrobial susceptibility patterns, Pediatric population